Ko-Kristalisasi Buah Nanas Sebagai Upaya Penggerak Kegiatan Ekonomi Di Pedesaan - Titiek Pujilestari (Balai Riset dan Standardisasi Industri Samarinda, 2016)
Pineapple (Ananas cosmosus L. Merr) is a perishable commodity and when the harvest abundant existence. Pineapple fruit contains high nutrition and complete, has very many benefits as an antioxidant and health. Development needs to be done pineapple juice processing as baked products in powder form in a way that has durability crystallization save. A fact that the number of urbanization and migration from rural to urban areas to earn a better income. To solve problems and improve the communities in rural areas required the development of economic sectors that are able to integrate the economy of farming and agricultural industries by utilizing local qualified